Government strategy for enhancing the infrastructure of international freight railway corridors: Economic and strategic considerations - Tymoshchuk, Yaroslav; Suray, Inna; Hrebeniuk, Halyna; Zadoia, Viacheslav; Selishchev, Sergii (Edelweiss Applied Science and Technology, 2025)
The article examines the state strategy for developing the infrastructure of international freight railway corridors in the European and Asia-Pacific regions from 2022 to 2023. It considers the impact of public investment on the formation of infrastructure projects through macroeconomic analysis. It describes programs that help optimize freight transport and stimulate trade development between continents. Public investment in the infrastructure of railway corridors in the EU has increased by 12% over the past five years, indicating a strategic interest in their further development. The article highlights the essence of international partnership and trade cooperation based on foreign investment to modernize railway networks. Special attention is paid to the strategic infrastructure goals for logistics corridors and transport hubs. The role of railway corridors passing through China and the European Union territory is identified. The competition between regions for leadership in transit hubs, economic influence, and control of transport corridors is investigated. At the micro level, trends in the formation of modal transport and the construction of heavy railway infrastructure are analyzed. The efficiency of the G7 countries in increasing the capacity of freight networks is studied. The problems of the states with regulatory protectionism measures have been identified. The article provides a comparative analysis of the leading companies in global freight corridors that are of strategic importance for the functioning of the economy.